A New Record of Ophiorrhiza trichocarpon Blume (Rubiaceae: Ophiorrhizeae) from Western Ghats, India: Another Source Plant of Camptothecin - Sibi, C. V.; Dintu, P. K.; Renjith, R.; Krishnaraj, M. V.; Roja, G.; Satheeshkumar, K. (Journal of Scientific Research, 2012)
Ophiorrhiza trichocarpon Blume is newly recorded from Western Ghats, India. A detailed description, with images and relevant notes are provided. Keywords: Ophiorrhiza trichocarpon; Camptothecin; Rubiaceae; Western Ghats; New Record; India. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.9378 J. Sci. Res. 4 (2), 529-532 (2012)